Lack of Temporal Impairment in Patients With Mild Cognitive Impairment - Mioni, Giovanna; Meligrana, Lucia; Perini, Francesco; Marcon, Michela; Stablum, Franca (Frontiers in Integrative Neuroscience, 2019)
In the present study, we investigate possible temporal impairment in MCI patients and the amount of temporal distortions caused by the presentation of emotional facial expressions (anger, shame, and neutral) in MCI patients and controls. Twelve older adults with MCI and 14 healthy older adults were enrolled in the present study. All participants underwent a complete neuropsychological evaluation. We used three timing tasks to tap temporal abilities, namely, time bisection (standard intervals lasting 400 and 1600 ms), finger tapping (free and 1-sec) and simple reaction time tasks. The stimuli used in the time bisection task were facial emotional stimuli expressing anger or shame to investigate a possible contribution of emotional information as previously observed on healthy adults. MCI patients showed temporal abilities comparable to controls. We observed an effect of facial emotional stimuli on time perception when data were analysed in term of proportion of long responses, and this result was mainly driven by the temporal overestimation when facial expression of anger was presented in controls. Results seem to suggest that the severity of the cognitive dysfunction accounts more than compromised internal clock for subjective temporal impairment